1997
DOI: 10.1093/ageing/26.suppl_2.49
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Incontinence in Nursing Home Residents: A Cross-National Comparison

Abstract: this study of different cultural approaches and strategies to evaluate and treat urinary incontinence may stimulate a public debate on the quality of care in nursing homes and promote the sharing of care practices designed to reduce urinary incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 15 publications
4
36
1
1
Order By: Relevance
“…[13][14][15][16][17][18] Cognitive impairment precedes urinary incontinence by approximately 6 years in Alzheimer's disease and by approximately 3 years in diffuse Lewy body disease. 19 Our strategy for urinary incontinence care favorably influenced the participants' physical and cognitive functions.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18] Cognitive impairment precedes urinary incontinence by approximately 6 years in Alzheimer's disease and by approximately 3 years in diffuse Lewy body disease. 19 Our strategy for urinary incontinence care favorably influenced the participants' physical and cognitive functions.…”
Section: Discussionmentioning
confidence: 99%
“…Age and sex were most frequently investigated (11 studies); in 8 out of 10 studies sex (i.e., being female) and age were associated with UI. Additionally, the UI prevalence rates in three studies 20,22,25 showed that nursing home residents with UI are usually older than residents without UI. Limited cognitive function was also a risk factor associated with UI in all 10 studies investigating this factor.…”
Section: Prevalence Of Uimentioning
confidence: 99%
“…International prevalence rates for European countries, Japan and USA were reported between 42·9–65·2% (Sgadari et al . ).…”
Section: Introductionmentioning
confidence: 97%